Facial Injuries in Handball: A Survey of Handball Coaches. Issue 3 (May 2019) - Hwang, Kun; Kim, Hun
Abstract : Abstract: The aim of this study was to investigate the occurrence of facial trauma in handball players in South Korea. Forty-one handball coaches responded to an 11-item standardized questionnaire. Twenty-three coaches (56.1%) stated that their players had experienced a facial injury and reported 56 patients. The nose was the most common site of the injuries (51.7%), followed by the eye (19.6%) and cheek (12.5%). The most common causes of nose injuries were being hit by a hand (26.8%), elbow (12.5%), and ball (8.9%). Most of the nose injuries were fractures (41.1%). The most common causes of the injuries were being hit by a hand (37.5%), elbow (30.3%), and ball (16.1%). The most common type of facial injury was fracture (41.1%), followed by contusion (26.8%), and laceration (21.4%). The most common position of the player was pivot (25.0%), followed by center back (21.4%), and right back (19.6%). Among the facial injuries experienced by pivots, the nose (12.5%) was the most common site, followed by the eye (8.9%). The most common causes of the injuries in pivots were being hit by a hand (12.5%) and an elbow (12.5%). The mean convalescence period after the facial injuries was 3.2 ± 1.6 weeks. No respondents stated that their players wore a mouthguard. Team doctors should be aware of the high frequency of nasal bone fractures and prepare for them. A suture set should be prepared for lacerations. If a player is hit in the eye by a ball, the possibility of retinal injury should be considered.